Crack Stopper for Local Damage and System Failure Focused on Environmentally Assisted Crack Propagation - Joaquin Delgado-Hernandez, David; Cho, Taejun (Recent Patents on Engineering, 2017)
Background: The proposed research work aims not only to advance the understanding on the effect of Environmentally Assisted Cracking (EAC) on the fracture resistance of the material, but preventing catastrophic failure due to EAC as well. Methods: The deterministic approach focuses on the understanding of the mechanics and mechanisms of the fracture failure for EAC on a material level. The design of the crack stopper on the expected spots of EAC is proposed and evaluated. Based on the submitted patent technology, an automatic lifting device against uneven settlement of deep sea infrastructure is presented, using different reactions of two enclosed and connected cylinders. Results: The device could lift the settled structure for seconds, while surrounding earth could flow into the lifted space due to hydrostatic pressure, resultantly the recovery of settlement and reduced stress around crack tip automatically without using external electronic power and devices. Conclusion: Therefore, it is expected that improved corrections for EAC, enhance safety maintenance with accelerated decreasing life-cycle costs.
Keywords: catastrophic failure